COLLABORATION BASED RECONFIGURATION OF PACKAGE SERVICE NETWORK WITH MULTIPLE CONSOLIDATION TERMINALS - Ko, Hyunjeung (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
The market competition of package deliveries in Korea is severe because a large number of companies have entered into the Koran market. A package delivery company in Korea generally owns and operates a number of service centers and consolidation terminals for high level customer service. However, some service centers cannot create profits due to low volume acting as the facilities raising the costs. This challenge can be overcome by collaboration strategy in order to improve its competitiveness. In this regard, this study suggests an approach to the reconfiguration of package service networks with respect to collaboration strategy. Thus, we propose a multi-objective nonlinear integer programming model and a genetic algorithm-based solution procedure for participated companies to maximize their profit. An illustrative numerical example in Korea is presented to demonstrate the practicality and efficiency of the proposed model.